Mapping the Integration of Computational Thinking in Mathematics Education: A Scopus-Based Bibliometric Analysis (2015–2025) - Eliska Juliangkary; I Nengah Suparta; I Made Ardana; Gusti Ayu Mahayukti (Media Pendidikan Matematika, 2025)
This study presents a comprehensive bibliometric analysis of research on Computational Thinking (CT) in mathematics education, based on Scopus-indexed publications from 2015 to 2025. CT—encompassing higher-order cognitive skills such as decomposition, pattern recognition, abstraction, and algorithmic thinking—has gained increasing relevance in 21st-century mathematics instruction. The study aims to map the development of research in this domain by analyzing seven key aspects: publication trends, author productivity, institutional productivity, journal productivity, international collaboration patterns, co-word relationships, and thematic evolution. A total of 165 English-language journal articles were analyzed using RStudio in conjunction with the Bibliometrix package. The results indicate a rapid annual publication growth rate of 23.11%, reflecting heightened global interest in the topic. Most publications resulted from collaborative research, with notable international partnerships, particularly involving Southeast Asian countries such as Indonesia. Frequently occurring keywords included "computational thinking," "students," and "engineering education," highlighting the emphasis on student-centered and interdisciplinary approaches. The co-word network and thematic mapping revealed strong linkages between CT and STEM education, project-based learning, curriculum development, and educational equity. Digital tools, including Scratch, robotics, and gamified learning platforms, shape the research landscape. However, persistent challenges remain, including limited teacher preparedness and unequal access to resources. This study contributes to educational innovation by illustrating how CT transforms mathematics pedagogy into a more contextual, technology-integrated, and collaborative practice. The findings are intended to inform educators, policymakers, and researchers in advancing curriculum reform and strategic research planning to enhance CT implementation across diverse educational contexts.